2022
DOI: 10.1002/jcla.24813
|View full text |Cite
|
Sign up to set email alerts
|

m6A‐related long noncoding RNAs predict prognosis and indicate therapeutic response in endometrial carcinoma

Abstract: Background N6‐methyladenosine (m6A) has been identified as the most common, abundant, and conserved internal transcriptional modification. Long noncoding RNAs (lncRNAs) are noncoding RNAs consisting of more than 200 nucleotides, and the expression of various lncRNAs may affect cancer prognosis. The impact of m6A‐associated lncRNAs on uterine corpus endometrial carcinoma (UCEC) prognosis is unknown. Methods In this study, UCEC prognosis‐related m6A lncRNAs were screened, bioinformatics analysis was performed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…These mRNAs regulated cell cycle progression accompanied by immune cell infiltration, which might lead to UCEC progression ( Zhao et al, 2022 ). Likewise, the findings indicated that the constituents of hazard models relying on the lncRNAs associated with m5C, m7G, or m6A could function as significant intermediaries of the immune milieu and promising prognosis biomarkers with therapeutic response in UCEC ( Gu et al, 2022 ; Sun et al, 2022 ; Chen et al, 2023 ; Zhou et al, 2023 ). Wang et al outline new insights into CNVs/SNVs in m6A regulatory genes which were associated with a negative impact on patient survival of EC and ultimately found that three genes, IGF2BP3, KIAA1429, and IGF2BP1 , were effective predictors of EC outcomes ( Wang et al, 2020 ).…”
Section: Network Resourcesmentioning
confidence: 93%
“…These mRNAs regulated cell cycle progression accompanied by immune cell infiltration, which might lead to UCEC progression ( Zhao et al, 2022 ). Likewise, the findings indicated that the constituents of hazard models relying on the lncRNAs associated with m5C, m7G, or m6A could function as significant intermediaries of the immune milieu and promising prognosis biomarkers with therapeutic response in UCEC ( Gu et al, 2022 ; Sun et al, 2022 ; Chen et al, 2023 ; Zhou et al, 2023 ). Wang et al outline new insights into CNVs/SNVs in m6A regulatory genes which were associated with a negative impact on patient survival of EC and ultimately found that three genes, IGF2BP3, KIAA1429, and IGF2BP1 , were effective predictors of EC outcomes ( Wang et al, 2020 ).…”
Section: Network Resourcesmentioning
confidence: 93%
“…In endometrial and cervical squamous cell carcinoma, SLC16A1-AS1’s upregulation and downregulation respectively are associated with overall survival [ 103 , 143 ], suggesting its role in prognostication in these cancers. Furthermore, in NSCLC [ 108 ], downregulation of SLC16A1-AS1 is linked to patient demographics, disease progression, and survival outcomes, highlighting its prognostic significance.…”
Section: Introductionmentioning
confidence: 99%